Why Collaborative Robots Must Be Social (and even Emotional) Actors. - Fischer, Kerstin (Techné: Research in Philosophy & Technology, 2019)
In this article, I address the question whether or not robots should be social actors and suggest that we do not have much choice but to construe collaborative robots as social actors. Social cues, including emotional displays, serve coordination functions in human interaction and therefore have to be used, even by robots, in order for long-term collaboration to succeed. While robots lack the experiential basis of emotional display, also in human interaction much emotional expression is part of conventional social practice; if robots are to participate in such social practices, they need to produce such signals as well. I conclude that if we aim to share our social spaces with robots, they better be social actors, which may even include the display of emotions. This finding is of empirical as well as philosophical relevance because it shifts the ethical discussion away from the question, how social collaborative robots should be, to the question, what kinds of human-robot collaborations we want.